Structure of highly active BSH enzyme with subordinated post-translational excision - Chand, Deepak; Panigrahi, Priyabrata; Ramasamy, Sureshkumar; Suresh, C. G. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Bile salt hydrolase; Mutagenesis; X-ray crystallography

Single crystal-to-single crystal site-selective postsynthetic metal exchange in a Zn-MOF based on semi-rigid tricarboxylic acid and access to bimetallic MOFs - Bajpai, Alankriti; Chandrasekhar, Pujari; Govardhan, Savitha; Banerjee, Rahul; Moorthy, Jarugu Narasimha (Chemistry-A European Journal, 2015)
The metal ions in a neutral Zn-MOF constructed from tritopic triacid H3L with inherent concave features, rigid core, and peripheral flexibility are found to exist in two distinct SBUs, that is, 0D and 1D. This has allowed site-selective postsynthetic metal exchange (PSME) to be investigated and reactivities of the metal ions in two different environments in coordination polymers to be contrasted for the first time. Site-selective transmetalation of Zn ions in the discrete environment is shown to occur in a single crystal-to-single crystal (SCSC) fashion, with metal ions such as Fe3+, Ru3+, Cu2+, Co2+, etc., whereas those that are part of 1D SBU sustain structural integrity, leading to novel bimetallic MOFs, which are inaccessible by conventional approaches. To the best of our knowledge, site-selective postsynthetic exchange of an intraframework metal ion in a MOF that contains metal ions in discrete as well as polymeric SBUs is heretofore unprecedented.
Keywords: coordination polymers; metal-exchange; metal-organic frameworks; Metathesis; X-ray crystallography

Structure and function of a highly active Bile Salt Hydrolase (BSH) from Enterococcus faecalis and post-translational processing of BSH enzymes - Chand, D. (Biochim Biophys Acta., 2018)
Bile Salt Hydrolase (BSH), a member of Cholylglycine hydrolase family, catalyzes the de-conjugation of bile acids and is evolutionarily related to penicillin V acylase (PVA) that hydrolyses a different substrate such as penicillin V. We report the three-dimensional structure of a BSH enzyme from the Gram-positive bacteria Enterococcus faecalis (EfBSH) which has manifold higher hydrolase activity compared to other known BSHs and displays unique allosteric catalytic property. The structural analysis revealed reduced secondary structure content compared to other known BSH structures, particularly devoid of an anti-parallel β-sheet in the assembly loop and part of a β-strand is converted to increase the length of a substrate binding loop 2. The analysis of the substrate binding pocket showed reduced volume owing to altered loop conformations and increased hydrophobicity contributed by a higher ratio of hydrophobic to hydrophilic groups present. The aromatic residues F18, Y20 and F65 participate in substrate binding. Thus, their mutation affects enzyme activity. Docking and Molecular Dynamics simulation studies showed effective polar complementarity present for the three hydroxyl (-OH) groups of GCA substrate in the binding site contributing to higher substrate specificity and efficient catalysis. These are unique features characteristics of this BSH enzyme and thought to contribute to its higher activity and specificity towards bile salts as well as allosteric effects. Further, mechanism of autocatalytic processing of Cholylglycine Hydrolases by the excision of an N-terminal Pre-peptide was examined by inserting different N-terminal pre-peptides in EfBSH sequence. The results suggest that two serine residues next to nucleophile cysteine are essential for autocalytic processing to remove precursor peptide. Since pre-peptide is absent in EfBSH the mutation of these serines is tolerated. This suggests that an evolution-mediated subordination of the pre-peptide excision site resulted in loss of pre-peptide in EfBSH and other related Cholylglycine hydrolases.
Keywords: autocatalytic processing; Bile salt hydrolase; molecular dynamics; Mutagenesis; Polar complementarity; X-ray crystallography

Structural studies on 10-hydroxygeraniol dehydrogenase: a novel linear substrate-specific dehydrogenase from Catharanthus roseus - Sandholu, Anand S.; Mujawar, Sharmila P.; Ramakrishnan, Krithika; Thulasiram, Hirekodathakallu V.; Kulkarni, Kiran (Proteins-Structure Function and Bioinformatics, 2020)
Conversion of 10-hydroxygeraniol to 10-oxogeranial is a crucial step in iridoid biosynthesis. This reaction is catalyzed by a zinc-dependent alcohol dehydrogenase, 10-hydroxygeraniol dehydrogenase, belonging to the family of medium-chain dehydrogenase/reductase (MDR). Here, we report the crystal structures of a novel 10-hydroxygeraniol dehydrogenase from Catharanthus roseus in its apo and nicotinamide adenine dinucleotide phosphate (NADP(+)) bound forms. Structural analysis and docking studies reveal how subtle conformational differences of loops L1, L2, L3, and helix alpha 9' at the orifice of the catalytic site confer differential activity of the enzyme toward various substrates, by modulating the binding pocket shape and volume. The present study, first of its kind, provides insights into the structural basis of substrate specificity of MDRs specific to linear substrates. Furthermore, comparison of apo and NADP(+) bound structures suggests that the enzyme adopts open and closed states to facilitate cofactor binding.
Keywords: 10-hydroxygeraniol dehydrogenase; iridoid biosynthesis; medium-chain dehydrogenase; monoterpene indole alkaloids; reductase; X-ray crystallography

Dynamic coupling analysis on plant sesquiterpene synthases provides leads for the identification of product specificity determinants - Singh, Sneha; Thulasiram, V, Hirekodathakallu; Sengupta, Durba; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2021)
Sesquiterpene synthases catalyse cyclisation of farnesyl pyrophosphate to produce diverse sesquiterpenes. Despite utilising the same substrate and exhibiting significant sequence and structural homology, these enzymes form different products. Previous efforts were based on identifying the effect of divergent residues present at the catalytic binding pocket on the product specificity of these enzymes. However, the rationales deduced for the product specificity from these studies were not generic enough to be applicable to other phylogenetically distant members of this family. To address this problem, we have developed a novel approach combining sequence, structural and dynamical information of plant sesquiterpene synthases (SSQs) to predict product modulating residues (PMRs). We tested this approach on the SSQs with known PMRs and also on sesquisabinene synthase 1 (SaSQS1), a SSQ from Indian sandalwood. Our results show that the dynamical sectors of SSQs obtained from molecular dynamics simulation and their hydrophobicity and vicinity indices together provide leads for the identification of PMRs. The efficacy of the technique was tested on SaSQS1 using mutagenesis. To the best of our knowledge, this is a first technique of this kind which provides cues on PMRs of SSQs, with divergent phylogenetic relationship. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: molecular dynamics; Product specificity; Sesquiterpene synthases; Statistical coupling analysis; X-ray crystallography

Synthesis, characterization, crystal structure, in silico and computational studies on a novel Schiff base derived from α-chlorocinnamaldehyde and 4-aminoantipyrine - Adimudo, Hillary Chijioke; Agu, Chidike Justus; Okenyeka, Obinna U.; Eddy, Nnabuk O.; Dim, Ebubechukwu Nnamdi; Dege, Necmi; Bonardd, Sebastian; Vanka, Kumar; Ibezim, Akachukwu; Idika, Digbo Iku; Diaz, David Diaz; Obasi, Nnamdi Lawrence (Journal of Molecular Structure, 2023)
Schiff base, 4-(((1E,2Z)-2-chloro-3-phenylallylidene)amino)-1,5-dimethyl-2-phenyl-1,2 -dihydro-3H-pyrazol-3-one (1) was synthesized by condensation reaction of 4-aminoantipyrine and & alpha;-chlorocinnamaldehyde. The compound was characterized using Fourier-transform infrared spectroscopy (FT-IR), ultraviolet (UV)-visible spectroscopy, proton and carbon nuclear magnetic resonance spectroscopy (1H/13C NMR) and single-crystal X-ray diffraction analysis (SC-XRD). Density functional theory (DFT) was used to compute molecular parameters and also compared them with experimental data. The X-ray diffraction data revealed that the compound crys-tallizes as a monoclinic crystal system with a space group of C2/c and Z = 8, and is stabilized by C12-H12MIDLINE HORIZONTAL ELLIPSISO1, and C8-H8AMIDLINE HORIZONTAL ELLIPSISO1 intramolecular hydrogen bonds. The presence of a distinctive azomethine C = N bond length N3-C12 of 1.283(3) & ANGS;, and 1640 cm-1 stretching vibration in the FT-IR spectrum are evidence of the formation of a Schiff base. The computational result indicates that the ionization energy (IE), and electron affinity (EA) values for the molecule are 4.025 and 2.110 eV, respectively. The positive value of EA suggests that the addition of an electron to the molecule would be an exothermic process. The evaluated energy is relatively low and is an expression of the ease of electron transfer from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO). Hirsfeld surface map over dnorm and curvedness surface indicated the presence of 7C-7C stacking while the shape factor index suggests donor and acceptor intermolecular C-H-7C. Analysis of Hirsfeld surfaces concerning the fingerprint indicated a minimal contribution from the de -di pair and reveals H–H as a major contribution to the Hirsfeld surface. However, the molecular packing did not confirm H–H as a significant contributor the packing. Docking calculations on the compound showed average theoretical binding energies toward aromatase (-5.99 & PLUSMN; 0.34 kcal/mol) and fibroblast growth factor receptor (FGFR) (-17.57 & PLUSMN; 6.85 kcal/mol), indicating binding interactions with both protein targets.
Keywords: Computational studies; molecular modeling; Schiff base; X-ray crystallography

4-aminoantipyrine linked bis-1,2,3-triazole based probes for Cu(II) sensing - Lal, Bajrang; Kumar, Sachin; Tittal, Ram Kumar; Singh, Gurleen; Singh, Jandeep; Ghule, Vikas D.; Mathpati, Ramling S.; Sabane, Jagjivan K. (Journal of Molecular Structure, 2024)
Herein, two molecular probes of 4-aminoantipyrine-linked bis-1,2,3-triazoles have been studied for metal ion sensing applications. The crystal structure of one of the probes named as 4,4 `-((4,4 `-(((1,5-dimethyl- 3- oxo- 2- phenyl- 2,3- dihydro- 1H- pyrazol- 4-yl) azanediyl) bis(methylene))bis(1H-1,2,3-triazole-4,1-diyl))bis(methylene))dibenzonit rile (3b) crystalizes in Monoclinic crystal system in P 1 21/n 1 space group. Both probes responded more strongly and selectively to Cu(II) than other tested metal ions (K+, Na+, Mg2+, Ba2+, Ca2+, Cr3+, Mn2+, Co2+, Zn2+, Cd2+, Ni2+, Hg2+, and Pb2+). Job's plot suggested a 1:1 stoichiometric ratio of ligand and metal ion. Both probes showed an association constant of 2.48 x 10(3) M-1 and 3.73 x 10(3) M-1 through Benesi-Hildebrand (B-H) plot. The geometries of both probes and their complexes were optimized by DFT using B3LYP/6-311 G(d,p) and B3LYP/LanL2DZ basis sets, and properties were supported by Mulliken atomic charge and Molecular electrostatic potential. Molecular docking on both probes and their complexes with Type-II topoisomerases(PDB ID: 4G0V) protein was conducted to foretastes anticancer activity.
Keywords: 2; 3-Triazole; 4-aminoantipyrine; and Molecular docking; Bis-1; Cu2+ Sensor; DFT; X-ray crystallography

Structure of epoxide hydrolase 2 from Mangifera indica throws light on the substrate specificity determinants of plant epoxide hydrolases - Bhoite, Ashwini; Gaur, Neeraj K.; Palange, Megha; Kontham, Ravindar; Gupta, Vidya; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2024)
Epoxide hydrolases (EHs) are a group of ubiquitous enzymes that catalyze hydrolysis of chemically reactive epoxides to yield corresponding dihydrodiols. Despite extensive studies on EHs from different clades, generic rules governing their substrate specificity determinants have remained elusive. Here, we present structural, biochemical and molecular dynamics simulation studies on MiEH2, a plant epoxide hydrolase from Mangifera indica. Comparative structure-function analysis of nine homologs of MiEH2, which include a few AlphaFold structural models, show that the two conserved tyrosines (MiEH2Y152 and MiEH2Y232) from the lid domain dissect substrate binding tunnel into two halves, forming substrate-binding-pocket one (BP1) and two (BP2). This compartmentalization offers diverse binding modes to their substrates, as exemplified by the binding of smaller aromatic substrates, such as styrene oxide (SO). Docking and molecular dynamics simulations reveal that the linear epoxy fatty acid substrates predominantly occupy BP1, while the aromatic substrates can bind to either BP1 or BP2. Furthermore, SO preferentially binds to BP2, by stacking against catalytically important histidine (MiEH2H297) with the conserved lid tyrosines engaging its epoxide oxygen. Residue (MiEH2L263) next to the catalytic aspartate (MiEH2D262) modulates substrate binding modes. Thus, the divergent binding modes correlate with the differential affinities of the EHs for their substrates. Furthermore, long-range dynamical coupling between the lid and core domains critically influences substrate enantioselectivity in plant EHs.
Keywords: Enantioselectivity; Epoxide hydrolase; molecular dynamics simulation; Regioselectivity; X-ray crystallography